THE FORMATION OF ISLĀMIC LAW - Akhmedov Burkhan Abdurakhmonovich (Western European Studies, 2024)
In the initial stage, legal institutions existed in an undeveloped form in the Islāmic state, and the moral tasks and sectarian figure of Islām were harmonious and harmonious with each other. Islāmic law began to take shape in the 1st century of the Hijri and rose to the stages of development in the 2nd and 3rd centuries of the Hijri. At the beginning of the 2nd century A.H., the first legal schools (madhhabs) began to appear, and the newly formed Islāmic society managed to build its primary legal and legal institutions.
Keywords: Islāmic law; fiqh; madhhab; sunnah